Fostering Entrepreneurial Values in Early Childhood Education: A Case Study of Craft-Making and Role-Playing Activities in Bandung - Nurhayati, Sri; Millenia, Dian (PIAUD Universitas Islam Negeri Sunan Kudus, 2024)
This study examines the integration of entrepreneurial values in early childhood education through craft-making activities and role-playing as sellers and buyers in a market-like setting at an early childhood education center in Bandung. Using a qualitative case study approach, the research combines observation, interviews, and document analysis. The findings reveal that key entrepreneurial values fostered through these activities include creativity, independence, perseverance, social interaction, honesty, and curiosity. Additionally, significant behavioral changes were observed in the children, such as increased self-confidence, enthusiasm, and active engagement, highlighting the program’s success in cultivating an entrepreneurial mindset. The study also underscores the critical role of educators as facilitators and the importance of parental involvement in ensuring the program’s effectiveness. Challenges identified during the study involved managing children’s frustration during the craft-making process and sustaining parental engagement. Consistent with prior research on entrepreneurship education, this study emphasizes the value of experiential, hands-on learning in early childhood. The findings have important implications, suggesting that child-centered, practical activities can be pivotal in nurturing the next generation of innovative and resilient entrepreneurs. Future research should explore the long-term impacts of such programs and investigate their effectiveness across diverse educational settings to contribute to the broader discourse on entrepreneurship education in early childhood.